2022
DOI: 10.1155/2022/5131170
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Radiomics with Genomics for Non-Small Cell Lung Cancer Survival Analysis

Abstract: Purpose. The objectives of our study were to assess the association of radiological imaging and gene expression with patient outcomes in non-small cell lung cancer (NSCLC) and construct a nomogram by combining selected radiomic, genomic, and clinical risk factors to improve the performance of the risk model. Methods. A total of 116 cases of NSCLC with CT images, gene expression, and clinical factors were studied, wherein 87 patients were used as the training cohort, and 29 patients were used as an independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In the era of modern personalized medicine, integrated multiomics approaches offer improved diagnostic accuracy and precise predictions. The integrated model combining radiomics with genomics outperformed either one alone in predicting prognosis or assessing postoperative recurrence risk in NSCLC [ 30 , 31 ]. However, no previous studies have integrated radiomics and genomics to predict the risk of RP in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…In the era of modern personalized medicine, integrated multiomics approaches offer improved diagnostic accuracy and precise predictions. The integrated model combining radiomics with genomics outperformed either one alone in predicting prognosis or assessing postoperative recurrence risk in NSCLC [ 30 , 31 ]. However, no previous studies have integrated radiomics and genomics to predict the risk of RP in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…They used CNNs to analyze images and Cox regression to train the survival model. Chen et al [32] suggested predicting cancer prognosis using radiological imaging, gene expression, and clinical risk factors. They employed autoencoders as a means to regenerate genomic features for gene expression analysis.…”
Section: Related Workmentioning
confidence: 99%
“…[42] L3 Molecular subtype - Yamamoto, S. et al [114] Medulloblastoma M1 Molecular subtypes - Dasgupta, A. et al [115] Renal Cancer R1 Prognosis Prediction Early fusion Schulz, S. et al [44] Colorectal cancer C1 metastasis prediction Early fusion Zhao, J. et al [43] Lung cancer L4 Recurrence prediction Intermediate fusion Jia, L. et al [116] Brain cancer B4 Prognosis prediction Intermediate fusion Cui, C. et al [117] Lung cancer L5 Prognosis prediction Early fusion Chen, W. et al . [118] …”
Section: Deep Learning Framework For Radiology-genomics Fusionmentioning
confidence: 99%